Pengaruh Profitabilitas, Leverage, Corporate Governance, dan Karakter Eksekutif pada Tax Avoidance - Nugrahitha, I Made Aditya; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Tax Avoidance is an attempt to avoid taxes by using loopholes in the government tax regulations. This study is proposed to determine the relationship between profitability, leverage, corporate governance, and executive character on tax avoidance. Tax avoidance measurement in this research uses cash effective tax rate (CETR). CETR in question is cash used for financing the tax expense divided by profit before tax. The research was conducted on companies incorporated in the Corporate Governance Forum of Indonesia which was included in the rating of Corporate Governance Perception Index (CGPI) and Indonesia Stock Exchange from 2011 to 2015 period. The number of samples obtained is 40 companies using purposive sampling. Multiple linear regression used as a technique in data analysis in this research. The results shows that profitability does not affect tax avoidance, leverage, corporate governance and executive character has a positive effect on tax avoidance. Keywords: tax avoidance, profitability, leverage, corporate governance, executive character.